Marginal analysis in tactical enterprise management - Herasimovich, A. M.; Mykhalska, O. L. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Analytical capacities of the method for presentation of cost and income data, referred to as “marginal approach ”, are shown. The marginal analysis method using the breakeven point allows for deriving a number of measures required for effective decision-making at company level on reduction in sales without risks of losses, required profit rate, amount of sales required to cover non-cash (depreciation) costs over a period, sales required to have a certain amount of profit after taxation, choice of production method etc. Computations of the five indicators, characteristic for the marginal analysis, are made for a Ukrainian oil and fat enterprise: (i) safety margin, (ii) sales required for a certain amount of profit, (Hi) “cash balance point”, (iv) sales required to have a certain amount of profit after taxation (net profit), (v) “breakeven cost” Also, the gross income ratio measuring the profitability of a product is proposed as a separate toolfor analysis of managerial decisions in the situations where the correlation between the amount of sales and variable costs is not changing. It is concluded that the breakeven model, through breaking production costs by constant and variable costs and computing marginal profit, can measure the effect of production output and sales for profit rate, and marginal sales required by company to be profitable.